2011
DOI: 10.1152/japplphysiol.00744.2009
|View full text |Cite
|
Sign up to set email alerts
|

Elevated oxidative stress and endothelial dysfunction in right coronary artery of right ventricular hypertrophy

Abstract: Lu X, Dang CQ, Guo X, Molloi S, Wassall CD, Kemple MD, Kassab GS. Elevated oxidative stress and endothelial dysfunction in right coronary artery of right ventricular hypertrophy. J Appl Physiol 110: 1674 -1681, 2011. First published March 17, 2011 doi:10.1152/japplphysiol.00744.2009.-Remodeling of right coronary artery (RCA) occurs during right ventricular hypertrophy (RVH) induced by banding of the pulmonary artery (PA). The effect of RVH on RCA endothelial function and reactive oxygen species (ROS) in vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 39 publications
(62 reference statements)
1
21
0
Order By: Relevance
“…That these effects play a role in shaping the coronary arterial flow waveform was first suggested by Rumberger et al (54,55) on the basis of flow transients ("oscillations") observed in early systole and diastole in the left anterior descending artery of horses, features that are also evident in published waveforms from humans and other species (5,14,38,76). More recently, therefore, a number of one-dimensional (1D) or multiscale (i.e., combined 0D/1D) models of the coronary circulation, which are best suited to the study of wave propagation effects, have been described (25,45,52,57,58,71).…”
mentioning
confidence: 92%
“…That these effects play a role in shaping the coronary arterial flow waveform was first suggested by Rumberger et al (54,55) on the basis of flow transients ("oscillations") observed in early systole and diastole in the left anterior descending artery of horses, features that are also evident in published waveforms from humans and other species (5,14,38,76). More recently, therefore, a number of one-dimensional (1D) or multiscale (i.e., combined 0D/1D) models of the coronary circulation, which are best suited to the study of wave propagation effects, have been described (25,45,52,57,58,71).…”
mentioning
confidence: 92%
“…It has been recognized as an independent predictor to a variety of cardiovascular diseases such as hypertension [1], diabetes [2], atherosclerosis [3], chronic kidney disease [4], as well as in general population [5]. It has been reported that endothelial dysfunction of conduit or resistance arteries is often concurrent with myocardial hypertrophy in hypertensive model rats [6][7][8], angiotensin II-infused model rats [9] and model of swines with aortic banding [10]. The association between cardiac hypertrophy and impaired endothelial function has also been reported in humans of chronic kidney disease [11], atherosclerosis [3] and nevertreated hypertensive patients [12].…”
Section: Introductionmentioning
confidence: 99%
“…These findings further support NADPH oxidase as a functionally relevant source of ROS for regulating coronary vascular tone. As both adenosine and ROS are generated and released under pathophysiological conditions [9,65] and generated ROS mainly exerts a detrimental influence on the coronary vasculature [54][55][56], future studies addressing the role of A 2A AR in ROS-mediated coronary vascular tone regulation in pathophysiological conditions will bring us greater insights into mechanisms underlying ischemic heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…This heterogeneity might be due to vasoconstrictor ROS vs. vasodilator ROS [29,31] generated from different vascular beds (coronary vs. renal artery) [34,37]. Furthermore, in the coronary vasculature, the varying effects of ROS may depend on which source ROS are generated from (NADPH vs. uncoupled NO synthase) [31,52,53] or the pathophysiological conditions [32,52,53], e.g., diabetes, and the right ventricular hypertrophy [54][55][56]. In accordance with our previous studies [37], the effect of ROS scavenging with EUK134 was comparable with the effect of Nox2 inhibition with gp91 ds-tat in WT isolated hearts (P=0.24), suggesting that the majority of ROS generated by adenosine is likely from Nox2, which leads to increases in coronary flow.…”
Section: Adenosine-induced Increase In Coronary Flow Is Mediated In Pmentioning
confidence: 99%